2000
DOI: 10.1007/pl00008508
|View full text |Cite
|
Sign up to set email alerts
|

Sensory receptors and surface ultrastructure of trypanorhynch cestodes

Abstract: The scolices of six different trypanorhynch species--Heteronybelinia alloiotica (Dollfus, 1960), Pseudolacistorhynchus noodti Palm, 1995, Otobothrium cysticum (Mayer, 1842), O. penetrans Linton, 1907, Poecilancistrum caryophyllum (Diesing, 1850), and Prochristianella hispida (Linton, 1890)--were examined for surface morphology and the occurrence of sensory receptors. Filamentous microtriches with different internal ultrastructural features were found. Acerosate, hook-like, and spiniform microtriches were detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
72
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(77 citation statements)
references
References 31 publications
3
72
1
1
Order By: Relevance
“…PALM et al (2000) reported a massive infection by O. cysticum (=Otobothrium sp.) plerocerci in the musculature of Peprilus burti Fowler, 1944 andP.…”
Section: Discussionmentioning
confidence: 99%
“…PALM et al (2000) reported a massive infection by O. cysticum (=Otobothrium sp.) plerocerci in the musculature of Peprilus burti Fowler, 1944 andP.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have T revealed that all the cestode species examined possess microtriches in larval and adult stages, and that they are probably of universal occurrence (Palm et al, 2000;Žd'ãrská and Nebesárõvá, 2005;Radha, et al, 2006;Poddubnaya et al, 2007 andLevron, 2008).…”
Section: Introductionmentioning
confidence: 94%
“…Rothman (1963) and Hayunga (1991) proposed an anchoring function of the caps and a nutritional function for the bases. Palm et al (2000), on the other hand, considered the possibility of multiple functions. In P. torulosus, the resorptive part of the tegument is lower than that of P. macrocephalus, where filamentous microtriches are distributed on the whole anterior part of the scolex and suckers (Žďárská and Nebesářová 1999a).…”
Section: Figs 9-12mentioning
confidence: 99%